Screen-Printed Ceramic MEMS for Metal Oxide Gas Sensor - Oleg Kul; Alexey Vasiliev; Andrey Nikitin; Anna Dmitrieva; Alexandr Bolshakov (Proceedings, 2024)
We developed a new approach to the fabrication of MEMS (Microelectromechanical system) substrates for gas sensors. This full screen-printing approach consists in the application of sacrificial material, which is solid at the near-room temperature of printing and becomes powder after firing of the elements of the sensor and, therefore, can be removed from under the suspended elements of the MEMS structure in an ultrasonic bath. The glass–ceramic MEMS is a cantilever structure equipped with a Pt-based microheater on the end edge with the sensing layer. Screen-printing provides cheap fabrication, robustness, and low power (~120 mW at 450 °C) for the sensing element.